Effects of regulated aerated irrigation on growth and yield of rice - LUO Tongcheng; TANG Yizhou; ZHANG Wenping; PENG Feiyu; HU Deyong; JIANG Zhengyi; PENG Bo (Guan'gai paishui xuebao)
【Objective】 Soil anaerobicity is a common abiotic stress in fine-textured soils that adversely affects crop growth. Aerated irrigation, achieved by adding air bubbles to irrigation water, is a technique to mitigate soil anaerobicity. This study investigates the effect of regulated aerated irrigation on rice growth, physiological traits at different growth stages, as well as grain yield. 【Method】 The experiment was conducted in pots using the Zhongzao 39 rice variety as model plant. The controlled irrigation was implemented by keeping soil moisture at 80%-100% (T1) or 60%-80% (T3) of the field capacity during late-tillering stage; at 80%-100% at late-tillering and booting stage (T2); at 60%-80% during late-tillering stage and 80%-100% during booting stage (T4); at 80%-100% during middle and late tillering stages (T5), at 80%-100% from middle tillering stage to booting stage (T6), at 80%-100% during mid-tillering stage and 60%-80% during late tillering stage (T7), at 80%-100% during mid-tillering and booting stages and 60%-80% during later tillering stage. During non-controlled stages, all treatments kept a thin water layer at the depth of 0-30 cm on the soil surface. The control (CK) was conventional flooding irrigation by keeping a 0-30 cm of water layer on the soil surface. For each treatment, we measured abscisic acid (ABA), peroxidase activity (POD), pollen viability, OsFKF1 gene expression and grain yield. 【Result】 Compared with CK, the treatments significantly increased pollen viability, OsFKF1 expression at the heading and flowering stages, and grain yield. T3, T2 and T8 achieved the highest pollen viability (83.28%), OsFKF1 expression (2.96), and grain yield (83.908 g/plant), respectively. ABA activity in roots and leaves, and POD activity in leaves, at the mid-tillering stage differed significantly between treatments. Compared with CK, the treatments reduced ABA in roots at the mid-tillering stage by 16.73%-23.69% and POD activity in leaves at the late-tillering stage by 19.91%-66.70%; conversely, they increased ABA in roots at the booting stage by 1.37%-63.52%. At the mid-tillering stage, T1—T4 reduced POD activity in roots by 70.36%-71.55%, whereas T5—T8 increased POD activity in roots by 2.53%-7.00%. Multiple linear regression analysis showed that the treatments increased ABA in roots at the late-tillering stage, reduced ABA in leaves at the late-tillering and booting stages, and decreased POD activity in leaves at the mid-tillering and late-tillering stages. These enhanced pollen viability and OsFKF1 gene expression at the heading and flowering stages, thereby increasing grain yield. 【Conclusion】 Among all treatments, T3 was the most effective in regulating ABA and POD, enhancing pollen viability, and improving rice grain yield, which reached 82.18 g/plant.